Textual origins of the indefinite article in Swedish - Skrzypek, Dominika (Versita, 2013)
The present paper studies the earliest stages of the grammaticalization of indefinite article in Old Swedish. The study is based on a corpus of Old Swedish texts and uses the model of grammaticalization as proposed by Heine 1997. The article en, etymologically related to the numeral ‘one’, is first used to mark new and salient discourse-referents and its primary function is cataphoric. However, en only fulfills this function when ocurring in a sentence-initial subject NP. In the course of the grammaticalization, neither the sentence-initial position nor the subject function of the NP are required to present new and salient discourse referents.
Keywords: indefiniteness; indefinite article; grammaticalization; language change; Swedish; nieokreśloność; rodzajnik nieokreślony; gramatykalizacja; zmiana językowa; język szwedzki